MAKNA DAN ARTI IKLAN ROKOK - Ni Ketut Sukanti (STIE BIITM, 2019)
Ads from the past, now and in the future make the most effective weapon for communicating to the public both social and commercial through print and electronic media, one of the advertisements that we often see and hear is cigarette advertisements using the word